PENGARUH PROMOSI LIVE TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA TIKTOK SHOP - Rumbha Wisang Jati; Ismatin Nisa Qomsiana Agustin; Sabrina Azahra (Cahaya Ilmu Bangsa, 2024)
This study aims to determine the effect of live streaming promotions on social media platforms and TikTok Shop online shopping, on consumer purchasing decisions. In this study, the sample used includes a general sample with the criteria of TikTok Shop application users who have made at least one purchase transaction. The research method is carried out through a quantitative approach, with the process of collecting primary and secondary data. This research was conducted on a total of 111 respondents. Primary data is obtained through the observation of research questionnaires, while secondary data is collected through the results of analysis on journals and academic books that are considered relevant. The results showed that the use of the TikTok Shop application related to promotion optimization had a significant influence on consumer purchasing decisions.